The Effect of Tax Minimization and Company Size on Transfer Pricing Moderated by Profit Management - Aini, Azhari; Rini, Yeni (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Transfer pricing is an internal corporate rule relating to the price of transactions carried out with related parties. The objective of the survey is to test and analyze the partial impact of tax minimization and corporate size on transfer pricing, as well as to test whether profit management moderates the impact of tax minimization and the size of the company on transfer pricing. Quantitative methods use corporate financial statements as secondary data. Mining companies listed in the EIB from 2019 to 2022 are the subject of research. Purposive sampling method is used to determine the sample, and twelve companies are selected. Data analysis using descriptive statistics, validity tests, classical assumption tests, linear regression analysis, and moderation tests through residual methods. Research results show that tax minimization has a significant positive impact on transfer pricing. The size of the company has a significant negative impact. Profit management has not been shown to moderate the impact of tax minimization and corporate size on transfer pricing.